Needs Assessment of Artificial Intelligence in Education at Vocational High School - Monica Fransisca; Renny Permata Saputri (AI Society & STMIK Indonesia, 2025)
This article aims to analyze the need for implementation of artificial intelligence in education at Vocational High School. Through technologies development and changing demands in industry, AI implementation in vocational high schools can be a solution to improve quality of education, prepare students with relevant skills, create more effective and personalized learning experience. This research uses quantitative approach with data collection through questionnaires distributed to teachers and students to identify perceptions and readiness towards the use of AI technology in learning process. The indicators analyzed include understanding of AI, perception of AI’s potential in education, readiness of technological infrastructure, challenges in AI implementation, readiness of human resources. The results shows that although there is great interest and potential to adopt AI in vocational high schools, there are challenges ahead. This article is expected to provide recommendations in planning an appropriate implementation of AI technology to improve the quality of education.